Innovation of Curriculum Management Based on Islamic Values in Increasing the Relevance of Education in Islamic Educational Institutions - Sa'adi, Ahmad (Afkaruna: International Journal of Islamic Studies (AIJIS), 2025)
Curriculum management is one of the crucial aspects of managing Islamic educational institutions. In the context of modern education, the challenges of globalization, digitalization, and the demand for curriculum relevance to societal needs are increasing. Innovation in curriculum management based on Islamic values serves as a strategic solution to address these challenges. This study aims to explore the concept, implementation, and impact of curriculum management innovation based on Islamic values in enhancing the relevance of education in Islamic educational institutions. The research method employed is library research, analyzing relevant academic sources. The findings indicate that integrating Islamic values, such as tauhid (monotheism), akhlaq (ethics), ukhuwah (brotherhood), and maslahah (public interest), into curriculum management can create a holistic learning system, shape students' character, and ensure educational relevance to contemporary demands and community needs. A curriculum designed based on Islamic values is not only oriented towards academic achievement but also aims to develop individuals with strong spirituality, 21st-century skills, and readiness to contribute to multicultural societies. Thus, curriculum management innovation based on Islamic values becomes a strategic key to making Islamic educational institutions more adaptive, relevant, and maintaining their Islamic identity amidst globalization.